In Silico Molecular Docking Studies and Pharmacokinetic Property Analysis of Phytocompounds from Camellia sinensis Targeting MCM2 Protein as Anti-Cancer Agent (Dhaka University Journal of Science, 2025)
Minichromosome Maintenance Complex Component 2 (MCM2) is a replicative helicase system subunit that is a major prognostic and proliferation marker for gastric, oral, breast, and colon cancers. During the replication procedure, it combines with histones named H3 and H4 by their N-terminal domain to help the assembly and disassembly of nucleosomes on DNA. MCM2 inhibition slows tumor cell growth and causes G0/G1 phase arrest, but it has little effect on cell apoptosis. Due to its complex structural composition and crucial involvement in DNA replication and regulation interface, MCM2 is a potential target for drug discovery. Traditional herbs are gradually gaining popularity. Beneficial functions of phytochemicals include low toxicity, low cost, availability, antioxidant activity, antibacterial action, regulation of detoxification enzymes, regulation of hormones, etc. The signaling pathway of many diseases alters simultaneously, and mutations happen in new ways, due to these reasons, discovering new drug candidates has become badly needed. Through Molecular docking study of compounds, pharmacokinetic property analysis, quantitative structure-activity relationship analysis, and drug-protein interaction against MCM2 protein, this work proposes phytochemical screening of the green tea plant (Camellia sinensis) to select the most potential drug compound to inhibit MCM2 protein.Dhaka Univ. J. Sci. 73(1): 67-76, 2025 (January)